Critical service encounters in UiTMCS: an exploratory investigation from students’ perspective using Critical Incident Technique (CIT) / Voon Boo Ho , Patricia Jussem and Firdaus Abdullah - Voon, Boo Ho; Jussem, Patricia; Abdullah, Firdaus (2002)
This exploratory study on the critical service encounters in UiTMCS was conducted to better understand the nature, causes and consequences of the University’s students’ favourable and unfavourable service encounters. The various underlying service evaluation criteria and service quality dimensions were identified with the applications of SERVQUAL Model. Critical Incident Technique (CIT) was used to investigate and understand the cause-course-outcome of each and every memorable service experience known as critical incident. There were 615 very satisfying and/or dissatisfying service encounters collected using personal interview, conveniently sampled to represent various major academic programmes in the University. The administered questionnaires contained few open-ended questions (capturing the critical incident) coupled with various close-ended questions (demographics).